Case Report: Changes in Cytokine Kinetics During the Course of Disease in a Japanese Patient With Multisystem Inflammatory Syndrome in Children - Takasago, Satoshi; Sakai, Aiko; Sugiyama, Masaya; Mizokami, Masashi; Hamada, Hiromichi; Ishizaka, Yukihito; Miyoshi-Akiyama, Tohru; Matsunaga, Akihiro; Ueno, Mikako; Shichino, Hiroyuki; Mizukami, Ayumi (Frontiers in Pediatrics, 2021)
Multisystem inflammatory syndrome in children (MIS-C) is a severe disease that is reportedly linked to coronavirus disease 2019. Affected patients present with gastrointestinal symptoms and cardiovascular dysfunction, in addition to Kawasaki disease‐like features, suggesting the potential for overlapping disease mechanisms. Kawasaki disease has been reported among individuals of East Asian ethnicities, whereas there is minimal clinical literature regarding the occurrence of MIS-C among individuals of Asian ethnicities. A few reports thus far have described changes in cytokine kinetics during the course of disease in patients with MIS-C. We followed the temporal cytokine kinetics in a 9-year-old Japanese girl who exhibited a classical trajectory of MIS-C. The patient exhibited right cervical swelling and pain, abdominal pain, vomiting, and lip reddening, which developed 31 days after she was diagnosed with severe acute respiratory syndrome coronavirus-2 infection. The patient was diagnosed with Kawasaki disease on her fifth day of illness; because she fulfilled the criteria for MIS-C, she was also diagnosed with this disease on her fifth day of illness. Her fever rapidly resolved upon administration of intravenous immunoglobulin, aspirin, and prednisolone. On the patient’s sixth day of illness, she developed acute myocarditis, which was treated with two diuretics and one vasodilator; the myocarditis ameliorated within a few days. Analyses of temporal kinetics for 71 serum cytokines revealed several patterns of cytokine changes that were consistent with the patient’s clinical course of disease. Importantly, there was a clear distinction between cytokines that did and did not decrease rapidly following post-treatment fever resolution. These findings may be useful for the assessment of disease status and selection of therapy in patients with similar symptoms; they may also provide insights for basic and clinical research regarding MIS-C.